A Differential Pattern of Batokine Expression in Perivascular Adipose Tissue Depots From Mice - Mestres-Arenas, Alberto; Villarroya, Joan; Giralt, Marta; Villarroya, Francesc; Peyrou, Marion (Frontiers in Physiology, 2021)
Depending on its anatomical placement, perivascular adipose tissue (PVAT) has been found to possess features more (e.g., aortic thoracic) or less (e.g., aortic abdominal) similar to brown/beige adipose tissue in mice. PVAT is thought to influence vascular function through the effects of adipose-secreted molecules on vessels. Brown adipose tissue was recently shown to play differential secretory role via secretion of the so-called batokines but the involvement of differential batokine production in PVAT brown/beige plasticity was unclear. The current study characterizes for the first time the expression of batokines at aortic thoracic PVAT (tPVAT) and aortic abdominal PVAT (aPVAT) in comparison with typical brown and white adipose depots, in basal and thermogenically-activated conditions. We found that both PVAT depots increased their expression of genes encoding the batokines BMP8B, FGF21 and KNG2 in response to cold, indicating that, under cold-induced thermogenic activation, both thoracic aorta and abdominal aorta would experience intense local exposure to these PVAT-secreted batokines. In contrast, the gene expression levels of Gdf15 and Vegfa were induced only in thoracic PVAT. Under short-term high-fat diet-induced thermogenic activation, the thoracic aorta would be specifically exposed to a local increase in PVAT-originating BMP8B, FGF21 and KNG2. Our data support the notion that acquisition of a brown/beige phenotype in PVAT is associated with upregulation of batokines, mainly BMP8B, FGF21 and KNG2, that can differentially target the vascular system.